Violencia intrafamiliar y su incidencia en el aprendizaje significativo de los y las estudiantes de los segundos años de bachillerato del colegio fiscal mixto Andrés F. Córdova de la Parroquia Rosa Zarate del Cantón Quinindé periodo lectivo 2015-2016 - Zambrano Quiñónez, Mercedes Doritza (2016)
The main objective of this research is focused on evaluating the Domestic Violence and its Impact on Meaningful Learning of students and second years of high school mixed school Andrés F. Cordova tax parish Rosa Zárate Quinindé Canton, period school from 2015 to 2016. Faced with this problem, a proposed solution that may lead to sensitize parents and prevent violence in homes through training workshops to strengthen family ties and enable students to enjoy a harmonious environment is reflected an emotional balance that you transfer to achieve meaningful learning and academic performance with an effective and comprehensive training. If there reigns an environment where dialogue and understanding in homes, children grow up safe and sound in their purposes. With the support of parents, teachers and responsibility of students, society changes radically, young people with a change of mind, critical, proactive and competent to function in society entities. The information collected in this research work is based on a critical perspective, theoretical and scientific, is based on social, educational and legal fields with a broad conceptual description of different authors and support of electronic documents and new information technologies and communication in order to take actions that benefit the students, parents of families, and members of the educational community, the same that runs through methods and techniques, ie, the statistical results are made according to the objectives, with the support of theoretical framework that are key parts in the investigation. The methodology applied transcends exploratory, descriptive and explanatory research for the design, inquiry applies not supported by the literature experimental or documentary and field or quantitative techniques and observation.